'Global restructuring' two decades on: Australia's relational economy in the twenty-first century. Issue 3 (3rd July 2018) - Martinus, Kirsten; Sigler, Thomas J.; O'Neill, Phillip; Tonts, Matthew
ABSTRACT: The Australian economy has changed dramatically over the past quarter of a century. The combination of neoliberal reform, increasing dependence on natural resources, the rise of the services economy and the restructuring of the nation's manufacturing sector has collectively transformed the national spatial economy. The publication of Fagan and Webber's Global Restructuring: The Australian Experience in 1994 provided an overview of the shifting geographies of the nation's economy as the country transitioned from relative stability during the 'long boom' after the Second World War into a period of rapid economic and policy change during the 1980s and 1990s. Despite the changes, Antipodean economic geography has, arguably, yet to gain new methodological or theoretical footing. The collection of papers in this special issue attempts to meet the challenge of a new direction to economic geography, reflecting on how this transition played out across different spatial and sectoral contexts, primarily in Australia. Papers documenting structural changes in the agricultural, automotive, creative industries, and energy sectors provide an understanding of how the convergence of political discourses, structural forces, and macroeconomic trends have interfaced with broad global shifts. Tying these together in the collection is a sustained focus on financialisation, particularly through globalised capital flows mediated through Australia's major cities. Thus the collection of papers in this special issue moves beyond Global Restructuring 's roots in structural political economy to a more globally nuanced perspective on industrial transformation. This editorial concludes by making the case for a direction in economic geography that emerges beyond a methodological Antipodean focus towards a more relational and practice-driven approach.